Effectiveness of rub ash waste as adsorbent household waste water - Eka Junaidi; I Nyoman Loka; Syarifa Wahidah Al Idrus; Baiq Fara Dwirani Sofia (Jurnal Pijar Mipa, 2022)
This study aims to determine the effectiveness of rice husk ash as an adsorbent to reduce phosphate levels in household wastewater and inexpensively. This research is an experimental laboratory research using the spectrophotometric method. Research data can be obtained through a series of experimental stages, including 1). Preparation of phosphate standard solution curve, 2). Determination of phosphate content before and after passing the adsorbent for the analyzed sample, 3). Determine the effectiveness of adsorbents in reducing phosphate levels in household wastewater. The effectiveness of rice husk ash as an adsorbent can be determined by comparing the phosphate levels before and after household wastewater is passed to the adsorbent. The magnitude of the reduction in phosphate content indicates the amount of phosphate adsorbed on the ash. Based on the experimental results, it is known that phosphate can be measured using a UV VIS Reign 1900 spectrometer at a wavelength of 693 nm. The standard phosphate solution curve was made based on the absorbance measurement of the series of standard phosphate solutions (0, 2, 4, 6, 8, and 10 ppm) used. In this study, the curve of the standard phosphate solution has the line equation: Y = 0.1723 X + 0.3823 with a correlation coefficient of 0.8633. In the equation of the line, Y indicates the absorbance value of the sample read on the spectrometer, while X indicates the concentration value of the substance being analyzed. Based on the equation of the curve line of the standard phosphate solution, it is used as a reference in determining the phosphate content of the sample by interpolating the absorbance that is read on the spectrometer owned by the sample and then determining the concentration value. Based on the calculation results, it was found that the ability to rice husk ash as an adsorbent to reduce phosphate levels in household wastewater was, on average, 52.54%. The ability of rice husk ash is still relatively small compared to the ability of rice husk ash as an adsorbent on heavy metals. In addition, phosphorus (P) as a constituent of phosphate has a smaller size (P diameter = 1.00) when compared to silica (diameter = 1.10), which is the largest composition in the ash. The difference in the size of the radius of phosphorus is smaller than that of silica. It is suspected as one of the causes of the phosphate content retained in the rice husk ash as an adsorbent is not too large. However, the percentage value of rice husk ash to reduce phosphate levels is still considered quite good as an adsorbent if the goal is to reduce phosphate levels from household wastewater that is discharged directly into the environment.